Bibliographi Cash Waqf Linked Sukuk (CWLS) Pada Perguruan Tinggi di Indonesia: Analisis Systematic Literature Review - Mahmud Yusuf; Abidir Rahman; Parman Komarudin (Management of Zakat and Waqf Journal (MAZAWA), 2022)
This research is a systematic literature review study which aims to find out the extent of studies conducted by university students in Indonesia related to Cash Waqf Linked Sukuk (CWLS) by focusing on the preparation of final assignments such as Thesis and Dissertation. The method used consists of three stages, namely collection, assessment, and presentation. The results of this study indicate that there are 11 final assignments that discuss Cash Waqf Linked Sukuk (CWLS) problems in universities throughout Indonesia. The writing of this final project has been started since 2019 and will reach its peak in 2021. From the many universities in Indonesia, students of UIN Syarif Hidayatullah Jakarta are the most enthusiastic in making Cash Waqf Linked Sukuk (CWLS) a study in their final project. Until now, studies of Cash Waqf Linked Sukuk (CWLS) in universities in Indonesia have concluded that Cash Waqf Linked Sukuk (CWLS) is basically in line with Islamic masqashid and does not conflict with positive law and Islamic law. Cash Waqf Linked Sukuk (CWLS) funds can also be used for various social purposes such as natural disaster recovery programs, community empowerment, procurement of health facilities, to financing MSMEs during the pandemic. In the future, Cash Waqf Linked Sukuk (CWLS) has a great opportunity to continue to grow in Indonesia. However, there are several factors that need to be considered in order to maximize this opportunity, including literacy, religiosity, income, and accessibility factors.